Degradation of atrazine by homogeneous photocatalysis using Fe(III)/UV/air system and evaluation of potential toxicity of atrazine and its metabolites - Keltnerová, Lucie (Jihočeská univerzita, 2017)
Atrazine photochemical degradation in homogeneous phase using Fe(III)/UV/air system was studied. Two toxicity assessments, a Lemna minor growth inhibition test and a Daphnia magna acute immobilisation test, were employed to test potential toxicity of atrazine and its degradation products. The occurrence of atrazine in rivers from the Vltava River basin was evaluated from the analyses performed by Povodí Vltavy, State Enterprise.
Degradation of atrazine by homogeneous photocatalysis using Fe(III)/UV/air system and evaluation of potential toxicity of atrazine and its metabolites
Keywords: atrazine; photochemical degradation; toxicity assessment; Daphnia magna; Lemna minor; Vltava river; atrazine; photochemical degradation; toxicity assessment; Daphnia magna; Lemna minor; Vltava river